Robust tracking control of a robot manipulator using a passivity‐based extended‐state observer approach. Issue 2 (10th November 2019) - Ali, Mohammed; Alexander, C.K.
Abstract : This study presents a combination of the robust passivity‐based controller (RPBC) and an extended state observer (ESO) for the tracking control of a three degree‐of‐freedom PUMA 500 robot manipulator under parameter variations and external disturbances. The dynamic model of the PUMA robot and its structural properties are analysed. The extra state in the ESO estimates the parameter variations and external disturbances in the control system. Then the RPBC cancels them in the control law. The stability of the proposed control system and the convergence of the observation errors are analysed. Simulations prove that the proposed controller is robust and tracks well under parameter variations, and external disturbances, validating the proposed control scheme.